Answer:
2y-x= -10
3y-x = 18
Explanation:
The correct option is . 2y-x = -10 , 3y-x = 18
one half x − 5 = 1/2 (x-5)
one third x + 6 = 1/3 *(x+6)
1/2 x-5 = 1/3x+6 =y
y= 1/2x-5
y = 1/3x+6
Now,
y=x/2 -5 equation 1
y = x/3 +6 equation 2
By taking L.C.M of the first equation we get:
y=x/2 -5
y= x-10/2
Now multiply both terms by 2.
2y=x-10
2y-x= -10
Now lets solve second equation:
Take L.C.M of the second equation:
y = x/3 +6
y=x+18/3
Multiply both sides by 3
3y= x+18
3y-x = 18
Therefore the system of equations we get is:
2y-x= -10
3y-x = 18 ....